2023
DOI: 10.1021/acsami.3c11656
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Trapping and Manipulation of Hollow Microparticles under Fluid Flow Using a Single-Lens Focused Ultrasound Transducer

Paul Wrede,
Amirreza Aghakhani,
Ugur Bozuyuk
et al.

Abstract: Microparticle manipulation and trapping play pivotal roles in biotechnology. To achieve effective manipulation within fluidic flow conditions and confined spaces, it is necessary to consider the physical properties of microparticles and the types of trapping forces applied. While acoustic waves have shown potential for manipulating microparticles, the existing setups involve complex actuation mechanisms and unstable microbubbles. Consequently, the need persists for an easily deployable acoustic actuation setu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Using a single acoustic piezoelectric transducer connected with a function generator and an amplifier, the authors demonstrated locomotion in both 2D and 3D artificial vasculatures (Figure 5a-e). Most recently, Wrede et al proposed the utilization of hollow borosilicate microparticles characterized by a rigid thin shell, which can be effectively trapped and manipulated using a single-lens focused ultrasound transducer (frequency of 2 MHz or 500 kHz) under physiologically relevant flow conditions [125]. These hollow microparticles provide stability and advantageous acoustic properties.…”
Section: Bubble-free Microrobotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a single acoustic piezoelectric transducer connected with a function generator and an amplifier, the authors demonstrated locomotion in both 2D and 3D artificial vasculatures (Figure 5a-e). Most recently, Wrede et al proposed the utilization of hollow borosilicate microparticles characterized by a rigid thin shell, which can be effectively trapped and manipulated using a single-lens focused ultrasound transducer (frequency of 2 MHz or 500 kHz) under physiologically relevant flow conditions [125]. These hollow microparticles provide stability and advantageous acoustic properties.…”
Section: Bubble-free Microrobotsmentioning
confidence: 99%
“…Ultrasound imaging is performed in the B-mode with a frequency of 40 MHz. Reprinted from Ref [125]. under the terms of the CC-BY 4.0 license.…”
mentioning
confidence: 99%